2004
DOI: 10.1002/jid.1080
|View full text |Cite
|
Sign up to set email alerts
|

Wider impacts of microfinance institutions: issues and concepts

Abstract: The paper distinguishes between a 'wider' definition of wider impacts (which takes into account feedbacks from impacts to institutional performance) and a 'narrower' definition, which does not. In respect of both definitions, the paper sets out a typology of the effects which need to be measured (cultural, economic, social and political) and of the levels at which each of these impacts needs to be assessed (local, regional and national). The purpose is not to set out a blueprint for specific studies but rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…The provision of microfinance to poor households in developing countries is one policy that has been suggested as a means to control rural out-migration (Zohir and Matin 2004). But empirical evidence on the relationship between access to credit and migration is limited, and the existing evidence suggests migration may only substitute for credit, and vice versa, in certain contexts.…”
Section: Conclude Thatmentioning
confidence: 99%
See 3 more Smart Citations
“…The provision of microfinance to poor households in developing countries is one policy that has been suggested as a means to control rural out-migration (Zohir and Matin 2004). But empirical evidence on the relationship between access to credit and migration is limited, and the existing evidence suggests migration may only substitute for credit, and vice versa, in certain contexts.…”
Section: Conclude Thatmentioning
confidence: 99%
“…More specifically, NELM theory proposes that migration and credit function as substitute solutions to a basic and crucial need for capital, and that migration serves as a substitute to insurance by providing a means of diversifying risk, in developing economies. By extension, both scholars and policy-makers have suggested that the development and expansion of credit and insurance markets in migrant-sending areas may stem out-migration (e.g., De Brauw and Rozelle 2008;Massey et al 2002;Rozelle et al 1999;Taylor et al 1996;Zohir and Matin 2004). Reviews of research on the causes of migration characterize absent or limited financial markets as ''fundamental causes'' of migration (Taylor et al 1996, p. 405), but studies exploring the relationship between access to credit or insurance markets and migration are mostly lacking.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is estimated that in 2007 there was a total of around 10,000 MFIs in the world (Ming-Yee, 2007), serving over 113 million clients. MFIs are seen to play a significant role in eradicating poverty in developing nations around the world (Caudill, Gropper, & Hartarska, 2009;Zohir & Matin, 2004). Some popular newspapers such as The Economist, the New York Times, and the San Francisco Examiner, have argued that microfinance could be the most important tool for reducing poverty.…”
Section: Microfinance and Social Developmentmentioning
confidence: 99%